Influence of perceived organisational support and supervisor support, and organisational commitment on casual dining restaurant employees’ intention to leave or stay - Mohamad Nashuki, Nasyira (2015)
The continuous growth of food and beverage services activities in Malaysia has been verified by the annual reports of the nation‟s economy. Predictions of growth indicate that profit will continue in the growing pattern in the near future. As a huge industry per se, it became a host to numerous types of food and beverage services establishments with one of them being casual dining restaurants. Due to the labourintensive nature, food and beverage services offer huge employment opportunities. Unfortunately, the condition also allows for the increasing possibilities of employee turnover. The high rate of employee turnover has become a concern as it troubles the managements due to the high cost that accompanies the turnover. With the interest to uncover the antecedents behind employee turnover and retention, academicians found that intention to leave is the best predictor of actual turnover while intention to stay may predict actual retention within a current workplace. In this study, perceived organisational support (POS), perceived supervisor support (PSS), and organisational commitment (OC) have been examined to determine their relationships with both intention to leave and intention to stay. The main objective is to investigate whether the key determinant that increases (or decreases) employees‟ intention to leave will also decrease (or increase) employees‟ intention to stay with the focus on employees of casual dining restaurants around Klang Valley. A total of 855 questionnaires were distributed to the respondents who were employed during data collection. After data screening, 428 data were used for further analysis. Descriptive analysis and structural equation modeling (SEM) were applied for data analysis. In descriptive analysis,descriptive results of respondents‟ socio-demographic profiles were calculated using SPSS Statistics version 21. SEM is analysed using AMOS version 21. There were two main stages involved in SEM, which were confirmatory factor analysis (CFA) in measurement model and path analysis in structural model. The result showed that OC was an influential factor in determining both employees‟ leaving intention and retention intention while POS had no significant relationship with either dependent variable. OC was negatively related to intention to leave and had positive relationship with intention to stay. On the other hand, PSS showed significant relationship only with intention to leave where they were negatively related. It was also determined that the factors that decreased (or increased) intention to leave did not necessarily increased (or decreased) intention to stay. In conclusion, the managements need to put extra effort in increasing employees‟ level of OC because committed employees who has hightendency of staying with the establishment would not only reduce costs, they would also help to meet the establishment‟s goals and targets.